Business, peacebuilding and sustainable development - Miklian, Jason; Alluri, Rina; Katsos, John E. (Business and peacebuilding series., 2019)
The intersection of business, peace and sustainable development is becoming an increasingly powerful space, and is already beginning to show the capability to drive major global change. This book deciphers how different forms of corporate engagement in the pursuit of peace and development have different impacts and outcomes. It looks specifically at how the private sector can better deliver peace contributions in fragile, violent and conflict settings and then at the deeper consequences of this agenda upon businesses, governments, international institutions and not least the local communities that are presumed to be the beneficiaries of such actions. It is the first book to compile the state-of-the-field in one place and is therefore an essential guide for students, researchers, policy-makers and practitioners on the role of business in peace. Without cross-disciplinary engagement, it is hard to identify where the cutting edge truly lies, and how to take the topic forward in a more systematic manner. This edited book brings together thought leaders in the field and pulls disparate strands together from business ethics, management, international relations, peace and conflict studies in order to better understand how businesses can contribute to peacebuilding and sustainable development. Before businesses take a deeper role in the most complicated and risky elements of sustainable development, we need to be able to better explain what works, why it works, and what effective business efforts for peace and development mean for the multilateral institutional frameworks. This book does just that.